Nitrous Oxide Adsorption and Decomposition on Zeolites and Zeolite-like Materials - Leonid M. Kustov; Sergey F. Dunaev; Alexander L. Kustov (Molecules, 2022)
Decomposition of N2O on modified zeolites, crystalline titanosilicalites, and related amorphous systems is studied by the catalytic and spectroscopic methods. Zinc-containing HZSM-5 zeolites and titanosilicalites with moderate Ti/Si ratios are shown to exhibit a better catalytic performance in N2O decomposition as compared with conventionally used Cu/HZSM-5 zeolites and amorphous Cu-containing catalysts. Dehydroxylation of the HZSM-5 zeolite by calcination at 1120 K results in an enhancement of the N2O conversion. The mechanism of the reaction and the role of coordinatively unsaturated cations and Lewis acid sites in N2O decomposition are discussed on the basis of the spectroscopic data.